2020
DOI: 10.1158/2326-6066.cir-20-0196
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome Associates with Immune Checkpoint Inhibition Outcomes in Patients with Advanced Non–Small Cell Lung Cancer

Abstract: The gut microbiome (GM) plays an important role in shaping systemic immune responses and influences immune checkpoint inhibitor (ICI) efficacy. Antibiotics worsen clinical outcomes in patients receiving ICI. However, whether GM profiling and baseline antibiotic can be a biomarker of ICI efficacy in advanced non–small cell lung cancer (NSCLC) remains unknown. We prospectively collected baseline (pre-ICI) fecal samples and clinical data of 70 Japanese patients suffering from advanced NSCLC and treated them with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
152
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 40 publications
8
152
3
Order By: Relevance
“…Interestingly, likewise to the role of the GM in other cancers, recent findings also indicate a relationship between the GM and the lungs [15]. Moreover, there is growing evidence demonstrating the association of the GM and its metabolome in ICI treatment response in NSCLC [16][17][18][19]. Indeed, not only the microbial cells but also their metabolites play a role in the stimulation of the immune response [5].…”
Section: Introductionmentioning
confidence: 91%
“…Interestingly, likewise to the role of the GM in other cancers, recent findings also indicate a relationship between the GM and the lungs [15]. Moreover, there is growing evidence demonstrating the association of the GM and its metabolome in ICI treatment response in NSCLC [16][17][18][19]. Indeed, not only the microbial cells but also their metabolites play a role in the stimulation of the immune response [5].…”
Section: Introductionmentioning
confidence: 91%
“…Accumulating data indicates that tumor responses to chemotherapies such as gemcitabine [ 38 ] and cyclophosphamide [ 126 ] depend on the gut microbiome. Several studies have shown a correlation between the gut microbiome composition and diversity and the efficacy of immunotherapy in patients with different tumor types, including melanoma, renal clear cell carcinoma, and lung cancer [ 4 , 15 , 17 , 127 , 128 , 129 , 130 ]. Recent data from melanoma patients revealed that the administration of stools from responders to immune checkpoint inhibitors (ICI) to non-responders can revert the primary resistance to these agents and lead to increased tumor infiltration by CD8 T cells [ 131 ], as previously suggested in pre-clinical studies [ 127 ].…”
Section: Microbiome and Antitumor Immunitymentioning
confidence: 99%
“…Moreover, the impact of the microbiota on cancer and cancer treatment is an emerging area of great interest [ 26 , 27 ]. In the era of novel immune-modulating agents, differential composition of the gut microbiota has been studied as one of the variables accounting for interpatient heterogeneity in ICB responses [ 28 , 29 , 30 , 31 , 32 ]. Additionally, lung cancer patients are frequently treated with antibiotics (ATB) and this intervention could modify or unbalance the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%